The Influence of Financial Literacy, Financial Attitudes, and Consumptive Behavior on the use of Fintech Dana Cita Pendidikan - Wati, Siska; Tambunan, Parulian (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This research aims to analyze the influence of financial literacy, financial attitudes, and consumer behavior on using Dana Cita Pendidikan fintech among the Universitas Pelita Bangsa students’ class of 2021. This research uses a quantitative approach, this research method uses a questionnaire method to find out respondents' answers. The research results show that: 1) Financial literacy significantly influences the use of Dana Cita Pendidikan fintech. 2) Financial attitudes also influence the use of Dana Cita Pendidikan fintech. 3) Consumptive behavior also influences the use of Dana Cita Pendidikan fintech among Universitas Pelita Bangsa students. These findings provide important insights for the development of financial education strategies and increasing the use of fintech among students.